Goat as the ideal climate-resilient animal model in tropical environment: revisiting advantages over other livestock species - Nair, M. R. Reshma; Sejian, V.; Silpa, M. V.; Fonsêca, V. F.C.; de Melo Costa, C. C. [UNESP]; Devaraj, C.; Krishnan, G.; Bagath, M.; Nameer, P. O.; Bhatta, R. (Springer Nature, 2021)
In the agriculture sector, livestock are considered extremely resilient to climate change and are tipped to play a significant role in ensuring food security to meet the increased demands of growing human population by 2050. Compared to other domestic species, goats are considered the ideal animal model for climate change due to its high thermal and drought resilience, ability to survive on limited pastures, and high disease resistance. This review is therefore a revisit to the advantages of rearing goats over other livestock species under current and future trends of changes in climate, particularly to cope with recurrent multiple stressors such as heat load, and lack of water and feed. In summary, goats, also called as poor man’s cow, are preferred by the small-scale landless farmers due to their low input and assured higher output system, as they require low initial investment, with minimum specialized facilities and labors. Furthermore, they perceive goats as better resilient animal to cope with multiple stressors such as heat load, and water and feed scarcity, and possess better skills to cope with bush, when compared with sheep and cattle. The unique capacity for employing behavioral plasticity and morphological features of goats gives them clear advantage over sheep and cattle, when coping with seasonal biotopes, and experiences of water and feed shortage. When facing with low-quality feed, they also are superior to cattle and sheep to digest dry matter and to recycle nitrogen. Additionally, goats have superior ability to desiccate feces and concentrate urine, when compared with sheep and cattle. These advantages make goat the go-to species for efficiently countering the adversities associated with climate change and to optimize appropriate economic return through sustained production. Therefore, goats are tipped to be the future animals with extreme potential to counter the projected alarming climate change impacts and expected to play a significant role in ensuring food security to meet the demands of the growing human population by the end of this century.
Keywords: Adaptation; Behavioral plasticity; Caprine; Thermal stress; Thermo-tolerance